Kaidah Tafsir Al-Siyaq Al-Khass Yurad Bih Al-‘Amm dalam Kitab Al-Qawa’id Al-Hisan li Tafsir Al-Qur’an - Mohammad Najih Mahmud (Kartika: Jurnal Studi Keislaman, 2026)
The Qur’an serves as a guide for life and a solution to human problems. However, certain messages within it may lead to interpretative ambiguities if not grounded in the proper scholarly framework of Qur’anic sciences one of which is rules of Qur’anic interpretation (qā’idah al-tafsīr). For instance, the verse that warns against consuming the property of orphans unjustly (Qur’an, Surah al-Nisa’: 10), can prompt interpretative questions. Does the punishment apply only to consuming orphan wealth? What about other actions? Employing a qualitative method and library research, this article examines several texts to address these questions. The findings affirm that applying rules of Qur’anic interpretation is crucial in interpreting the Qur’an. In the context of the aforementioned issues, the interpretative rule used is al-siyāq al-khaṣṣ yurād bih al-‘āmm, as outlined in the book al-Qawā’id al-Ḥisān. This rule means that a specific context can carry a universal implication although the wording appears specific, the intended message is general and widely applicable. From this discussion, two conclusions emerge concerning the general nature of such contexts: (i) other actions or words with similar intent or impact fall under the same ruling, and (ii) actions or words with greater harm or severity are likewise included."